Extended shelf life milk processing: Effect of cleaning in place (CIP) on the germination and attachment of Bacillus cereus spores - Buys, E.M. (Elna Maria) (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2018.